2021
DOI: 10.13057/biodiv/d220940
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of tithonia (Tithonia diversifolia) with fermentation using Lactobacillus plantarum and Aspergillus ficuum at different incubation times

Abstract: Abstract. Pazla R, Jamarun N, Zain M, Yanti G, Chandra RH. 2021. Quality evaluation of tithonia (Tithonia diversifolia) with fermentation using Lactobacillus plantarum and Aspergillus ficuum at different incubation times. Biodiversitas 22: 3936-3942. This research aimed to evaluate the nutritional quality of tithonia (Tithonia diversifolia) fermented using Lactobacillus plantarum and Aspergillus ficuum with different incubation times on nutritional content, digestibility, phytase enzyme activity, and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
1
27
2
1
Order By: Relevance
“…It can result in a decrease in the digestibility of the feed ingredients. Nutrient digestibility in this study is higher than that reported by Pazla et al (2021a), who compared nutrient digestibility of fermented T. diversifolia with L. plantarum and A. ficuum. This difference may be caused by different feed ingredients in each study.…”
Section: Trialcontrasting
confidence: 87%
“…It can result in a decrease in the digestibility of the feed ingredients. Nutrient digestibility in this study is higher than that reported by Pazla et al (2021a), who compared nutrient digestibility of fermented T. diversifolia with L. plantarum and A. ficuum. This difference may be caused by different feed ingredients in each study.…”
Section: Trialcontrasting
confidence: 87%
“…The higher the activity of phytase enzyme produced by microbes, the lower the phytic acid content (Reddy and Pierson 1994). In this study, phytase enzyme activity from L. bulgaricus was higher, but the activity of phytase enzyme produced by Lactobacillus plantarum in the fermented tithonia plant was (Pazla et al 2021b). The difference in values may be due to the type of lactic acid bacteria used.…”
Section: Phytase Enzyme Activitymentioning
confidence: 55%
“…Forage eaten by livestock undergoes a fermentative process in the rumen by rumen microbes [9], [10]. The main product of fermentation in the rumen is VFA (Volatile fatty acids) [11], [12]. VFA consists of acetate, propionate and butyrate [13].…”
Section: Resultsmentioning
confidence: 99%